الطن بطريق الإستئناف في الحكم القضائي ودوره في تعزيز المحاكمة العادلة في التشريع الجزائري - شلالي، رضا Shalali, Reda; لطرش، سلمى; عبدالرحمان، بن سالم أحمد (جامعة زيان عاشور الجلفة, 2021)
يعد الاستئناف الطريق العادي الثاني من طرق الطعن العادية في الأحكام القضائية الجزائية، ومؤداه اعتراض الطاعن على الحكم الصادر من محكمة درجة أولى على خلاف مصلحته، يبتغي من طعنه إعادة نظر موضوع الدعوى من جديد أمام جهة قضائية أعلى درجة وأكثر عددا وأعمق خبرة توصلا إلى إلغاء الحكم الصادر في حقه أو تعديله على هذا النحو يعد تطبيقا لمبدأ التقاضي على درجتين، الذي تبنته السياسة الجنائية الحديثة، ودرجت عليه أغلب الشرائع الجنائية المعاصرة، لتوفير الثقة والاطمئنان في العمل القضائي.
Appeal is the second normal way of appeal in criminal judicial rulings. it leads to the appellant's objection to the judgment issued by a court of first instance against his interest The object of his appeal is intended to reconsider the case Once again in front of a judicial authority of a higher degree and more numerous and deeper experience, leading to the cancellation or amendment of the judgment issued against him In this way, it is considered an application of the principle of two-degree litigation, which was adopted by modern criminal policy, and it is the norm in most contemporary criminal laws, to provide confidence and confidence in the judicial work.
Keywords: استئناف الأحكام -- الأحكام القضائية -- القوانين والتشريعات -- الجزائر